The solution of x^3-4x^2+x-4 = 0 has to be determined.

x^3-4x^2+x-4 = 0

=> x^2(x - 4) + 1(x - 4) = 0

=> (x^2 + 1)(x - 4) = 0

x^2 + 1 = 0

=> x^2 = -1

=> x = `+-sqrt(-1)`

=> x = `+-i`

x - 4 = 0

=> x = 4

**The solution of the equation x^3-4x^2+x-4 = 0 is {-i, i, 4}**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now